(untitled) (Journal of medical and pharmaceutical sciences, 2019)
Aim: This study is really aimed to explain the possibility of viewing the coronary arteries by transthoracic echocardiography and its importance in taking the diagnosis about non-specific chest discomfort like tightness or burning with back pain and others, to help patients & save their lives. Presentation: 40 years old male complains of intermittent recurrent chest tightness and back pain for 6 months ago , and had a non-specific electrocardiogram and normal echocardiogram findings, with hypertension of 160/98 mmHg discovered on the first visit to see a doctor that prescribed for him bisoprolol 5 mg tab per day and anxiolytic drugs , and while he was using these medicines he was suffered from new recurrence, therefore, echocardiogram examination for coronary arteries was done and revealed its walls thickening and stenosis. Conclusion: the conclusion of this study are revealing the transthoracic echocardiogram as a valuable non-invasive imaging technic for examination of the coronary arteries with clear detection of the walls thickening and lumens diameters, and it will contribute to putting a prevention plans for decreasing the myocardial infarctions and its complications.